2010
DOI: 10.1021/ma101031t
|View full text |Cite
|
Sign up to set email alerts
|

Binodal Compositions of Polyelectrolyte Complexes

Abstract: When oppositely charged polyelectrolytes are mixed below a critical salt concentration, their mixtures show macroscopic phase separation into a dilute and a dense, polyelectrolyte complex phase. Binodal compositions of the polyelectrolyte complexes have been measured experimentally using fluorescently labeled polyelectrolytes. We used fluorescein-labeled poly(acrylic acid) (PAA) of four different chain lengths (N = 20, 50, 150, and 510) to determine the binodal compositions of polyelectrolyte complexes of PAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

69
711
7
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(789 citation statements)
references
References 37 publications
69
711
7
2
Order By: Relevance
“…"# --value is also in good agreement with the stoichiometry found in ITC on the same compounds. We have found that stoichiometric PSS/PDADMAC mixtures without added salt form a viscous coacervate phase that sedimented rapidly [63,64]. Observed between glass slides, the coacervate appears as 5 µm droplets (Fig.…”
Section: Iii1 - Assessment Of the Pacts Technique Using Ion--containmentioning
confidence: 85%
“…"# --value is also in good agreement with the stoichiometry found in ITC on the same compounds. We have found that stoichiometric PSS/PDADMAC mixtures without added salt form a viscous coacervate phase that sedimented rapidly [63,64]. Observed between glass slides, the coacervate appears as 5 µm droplets (Fig.…”
Section: Iii1 - Assessment Of the Pacts Technique Using Ion--containmentioning
confidence: 85%
“…An example of these types of detailed binodal curves is shown in Figure 3 for the system of poly(acrylic acid) (PAA) in complex with poly(N,N-dimethylaminoethyl methacrylate) (PDMAEMA), in the presence of KCl [78]. The phase behavior of this system was analyzed only for a 1:1 stoichiometric (charge-neutral) mixture of PAA and PDMAEMA, rather than for the entire range of PAA-PDMAEMA-KCl composition space depicted in Figure 3b.…”
Section: Connecting Coacervate Phase Behavior With Materials Dynamicsmentioning
confidence: 99%
“…Despite these recent advances, VO theory continues to be used to explain experimental data because of its inherent simplicity and applicability for a wide range of systems. Recently, for example, Spruijt et al [10] adapted the VO theory to describe complexation behavior of charge-stoichiometric compositions of synthetic polyelectrolytes, poly(acrylic acid) (PAA) and poly(N,N-dimethylaminoethyl methacrylate) (PDMAEMA), and obtained good agreement with experiments. Priftis et al [34] have also used a modified version of the VO theory to explain complexation behavior in ternary systems composed of a polycation with two polyanions: (1) PAA with PDMAEMA and poly(allylamine) (PAH), and (2) PAA with PDMAEMA and poly(ethylenimine) (PEI).…”
Section: Introductionmentioning
confidence: 98%
“…Oparin's hypothesis has however been dismissed in modern theories of the origin of life, particularly after the discovery of DNA as the genetic material [7]. Most of the earlier studies on polyelectrolyte complexation focused on coacervation of natural polymers such as albumin and gelatin, but recent studies [2,3,[8][9][10][11][12] have extended this to the complexation of synthetic polyelectrolytes. Renewed scientific interest in polyelectrolyte complexation is due, in part, to its use in polyelectrolyte assemblies and multilayer films [13,14], which have many technological applications [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation